What are the features of this software?: an exploratory study - Paech, Barbara; Hübner, Paul; Merten, Thorsten (ICSEA 2014, 2014)
Application systems are often advertised with features, and features are used heavily for requirements management. However, often software manufacturers only have incomplete information about the features of their software. The information is distributed over different sources, such as requirements documents, issue trackers, user manuals, and code. In this paper, we research the occurrence of feature information in open source software engineering data. We report on a case study with three open source systems. We analyze what information about features can be found in issue trackers and user documentation. Furthermore, we study the abstraction levels on which the features are described, how feature information is related, and we discuss the possibility to discover such information semi-automatically.
Gesehen am 26.07.2018